High-endothelial cell-derived S1P regulates dendritic cell localization and vascular integrity in the lymph node - Simmons S; Sasaki N; Umemoto E; Uchida Y; Fukuhara S; Kitazawa Y; Okudaira M; Inoue A; Tohya K; Aoi K; Aoki J; Mochizuki N; et al. (eLife Sciences Publications Ltd, 2022)
While the sphingosine-1-phosphate (S1P)/sphingosine-1-phosphate receptor-1 (S1PR1) axis is critically important for lymphocyte egress from lymphoid organs, S1PR1-activation also occurs in vascular endothelial cells (ECs), including those of the high-endothelial venules (HEVs) that mediate lymphocyte immigration into lymph nodes (LNs). To understand the functional significance of the S1P/S1PR1-Gi axis in HEVs, we generated Lyve1;Spns2Δ/Δ conditional knockout mice for the S1P-transporter Spinster-homologue-2 (SPNS2), as HEVs express LYVE1 during development. In these mice HEVs appeared apoptotic and were severely impaired in function, morphology and size; leading to markedly hypotrophic peripheral LNs. Dendritic cells (DCs) were unable to interact with HEVs, which was also observed in Cdh5CRE-ERT2;S1pr1Δ/Δ mice and wildtype mice treated with S1PR1-antagonists. Wildtype HEVs treated with S1PR1-antagonists in vitro and Lyve1-deficient HEVs show severely reduced release of the DC-chemoattractant CCL21 in vivo. Together, our results reveal that EC-derived S1P warrants HEV-integrity through autocrine control of S1PR1-Gi signaling, and facilitates concomitant HEV-DC interactions.